Fault-Tolerant Network Topologies for Datacenters - Attia, Heba Mahmoud Helal (2017)
A Master of Science thesis in Computer Engineering by Heba Mahmoud Helal Attia entitled, "Fault-Tolerant Network Topologies for Datacenters," submitted in May 2017. Thesis advisor is Dr. Rana Ahmed. Soft and hard copy available. Embargo expires February 08, 2018.